To Stimulate or Inhibit? That Is the Question for the Function of Abscisic Acid - Humplík, Jan F; Bergougnoux, Véronique; Van Volkenburgh, Elizabeth (Trends in plant science, 2017)
Physiologically, abscisic acid (ABA) is believed to be a general inhibitor of plant growth, including during the crucial early development of seedlings. However, this view contradicts many reports of stimulatory effects of ABA that, so far, have not been considered in the debate concerning ABA's function in plant development. To address this apparent contradiction, we propose a hypothetical mechanism to explain how ABA might contribute to the promotion of cell expansion. We wish to overturn conventional views on ABA's role during juvenile plant development and put forward the idea that, as for other phytohormones, the role of ABA is determined by dose and sensitivity and ranges from stimulatory to inhibitory effects.
Keywords: hypocotyl; photomorphogenesis; Plant Development; Plant Growth Regulators; abscisic acid; etiolation; vývoj rostlin; Abscisic Acid; regulátory růstu rostlin; kyselina abscisová; Seedlings; semenáček; skotomorphogenesis